2011
DOI: 10.1097/ijg.0b013e3181e0799c
|View full text |Cite
|
Sign up to set email alerts
|

Does the Enlargement of Retinal Nerve Fiber Layer Defects Relate to Disc Hemorrhage or Progressive Visual Field Loss in Normal-tension Glaucoma?

Abstract: The enlargement of RNFLD in NTG was closely associated with DH occurrence and the deterioration of visual field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
56
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 21 publications
8
56
0
Order By: Relevance
“…24 One recent report showed that DH was more frequent in eyes with RNFL defect enlargement. 9 The authors of that study speculated that enlargement of RNFL defect causes damage or loss of capillaries at the border of a RNFL defect. This may be explained by ''collapse theory,'' which refers to structural alteration resulting in mechanical rupture of the vessels leading to DH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 One recent report showed that DH was more frequent in eyes with RNFL defect enlargement. 9 The authors of that study speculated that enlargement of RNFL defect causes damage or loss of capillaries at the border of a RNFL defect. This may be explained by ''collapse theory,'' which refers to structural alteration resulting in mechanical rupture of the vessels leading to DH.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Typically, DH develops in association with notching, progressive changes in the optic disc rim, localized retinal nerve fiber layer (RNFL) defects, and enlargement of localized RNFL defects. [6][7][8][9] Many studies have shown that rim notching or loss, focal RNFL defects, and corresponding localized and global visual field (VF) deterioration occur after DH. [10][11][12] Some studies have shown more pronounced progressive changes in the VF in eyes with recurrent DH compared to eyes with a nonrecurrent DH.…”
mentioning
confidence: 99%
“…4 However, DH has been observed more frequently in patients with normal-tension glaucoma (NTG) than in patients with high-tension glaucoma, [10][11][12] and in early rather than in late stages of disease. 2,13 Hemodynamic disturbances, including ischemic microinfarction in the optic nerve head, 14 disorders of retinal circulation, 15 decrease in capillary perfusion, 16 and primary vascular dysregulation (PVD) 17 also have been proposed as causes of DH; these support vascular factors having a significant role in the pathogenesis of DH.…”
mentioning
confidence: 99%
“…A history of migraine, narrower neuroretinal rim width at the baseline, low mean arterial ocular perfusion pressure, and the use of systemic beta blockers were independent risk factors for the occurrence of disc hemorrhage in treated NTG patients (74) . The occurrence of an enlarged RNFL defect was more frequent in NTG patients who presented with disc hemorrhage, and the location of the defect was in the same region as that of the disc hemorrhage (75) . Using serial EDI-OCT, Lee et al observed that deformation or disruption of the lamina cribrosa precedes the occurrence of disc hemorrhage.…”
Section: Disc Hemorrhagementioning
confidence: 82%